Indigenous Counseling: Khaul Syekh Mutamakkin As An Intervention Based On Local Wisdom In Pati Regency - Sri Maullasari (Department of Islamic Guidance and Counseling, 2021)
This paper aims to provide a conceptual framework regarding various local wisdoms in Pati district. More specifically on the intervention of Indigenous Counseling Khaul Syekh Mutamakkin; as a Local Wisdom-based Intervention in Pati District. Pati Regency has a tradition that is always held every year. This tradition is passed down from generation to generation. Tradition is also considered as people's belief in something. This activity is carried out as a form of expression of gratitude, commemorating an anniversary, and about commemorating the death of someone. All of these traditions can be used as Indigenous Counseling interventions. This implies that counseling is rooted in the knowledge system and community practice based on the place where individuals internalize the knowledge system and practice their behavior. Likewise, the tradition of Shaykh Mutamakkin's khaul which is a model of getting closer to God as a useful life philosophy. Even though it shows a Javanese cultural bias, it has become a form of daily spiritual practice that is still practiced by the Pati people.